Burden on caregivers of ventilator-dependent patients: A cross-sectional study. Issue 27 (July 2017) - Liu, Jui-Fang; Lu, Man-Chi; Fang, Tien-Pei; Yu, Hong-Ren; Lin, Hui-Ling; Fang, Der-Long
Abstract : Abstract: Caring for prolonged mechanical ventilation (PMV) patients imposes heavy psychological, physical, social, and financial burdens on caregivers. Currently, studies regarding the burden on caregivers of PMV patients are scant; therefore, the present study investigated the burden on caregivers of PMV patients. This cross-sectional study was approved by the Institutional Review Board of Zuoying Armed Forces General Hospital. A survey was conducted among the caregivers of PMV patients who were admitted to a chronic respiratory care ward (RCW) or were receiving home care from June to December 2010. The survey included basic demographic information of PMV patients and their caregivers and the Burden Assessment Scale scores for 4 domains comprising a total of 21 questions (physical burden, n = 5; psychological burden, n = 6; social burden, n = 6; financial burden, n = 4). Statistical analyses were conducted using the t test, 1-way analysis of variance with the Scheffé post hoc test, and the chi-square test, and P < .05 was considered statistically significant. A total of 160 caregivers (age, 50–53 years) were recruited (n = 80 each in the home care and RCW groups), and most of these caregivers were married women. Due to insufficient sleep, physical exhaustion, back pain, and caregiving, home caregivers had significantly higher physical burden levels than RCW caregivers ( P < .01). Home caregivers experienced higher physical burden levels than RCW caregivers. Therefore, clinical and professional support must be provided to home caregivers of PMV patients.